2023
DOI: 10.1073/pnas.2220148120
|View full text |Cite
|
Sign up to set email alerts
|

ARL6IP1 mediates small-molecule-induced alleviation of Alzheimer pathology through FXR1-dependent BACE1 translation initiation

Abstract: Exploring the potential lead compounds for Alzheimer’s disease (AD) remains one of the challenging tasks. Here, we report that the plant extract conophylline (CNP) impeded amyloidogenesis by preferentially inhibiting BACE1 translation via the 5′ untranslated region (5′UTR) and rescued cognitive decline in an animal model of APP/PS1 mice. ADP-ribosylation factor–like protein 6–interacting protein 1 (ARL6IP1) was then found to mediate the effect of CNP on BACE1 translation, amyloidogenesis, glial activation, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…Using luciferase‐based high‐throughput screenings, we have previously reported that some small molecules regulate amyloidogenesis, [ 16 ] which leads to the finding of kenpaullone (KEN) in the present study. We define that KEN promotes the 5′ untranslated region (5′UTR)‐dependent ADAM10 translation and alleviates amyloidogenesis in APP/PS1 mice, an animal model of AD.…”
Section: Introductionmentioning
confidence: 69%
See 4 more Smart Citations
“…Using luciferase‐based high‐throughput screenings, we have previously reported that some small molecules regulate amyloidogenesis, [ 16 ] which leads to the finding of kenpaullone (KEN) in the present study. We define that KEN promotes the 5′ untranslated region (5′UTR)‐dependent ADAM10 translation and alleviates amyloidogenesis in APP/PS1 mice, an animal model of AD.…”
Section: Introductionmentioning
confidence: 69%
“…Transcription inhibitor actinomycin D (ActD) or protein synthesis inhibitor cycloheximide (CHX) alone led to a reduced ADAM10 protein level, [ 26 ] whereas KEN‐induced ADAM10 enhancement was diminished in the presence of CHX but not ActD (Figure 2B ), suggesting an involvement of protein synthesis. It seemed that protein degradation machinery was not involved in this regulation, as the proteasomal inhibitor MG132 or the lysosomal inhibitor chloroquine (CQ) [ 16a ] failed to block KEN‐mediated augmentation of ADAM10 (Figure 2C ). Moreover, we excluded the possibility that CDKs/GSK‐3 played a role in ADAM10 regulation, as silencing of CDK5 or GSK‐3β alone did not change ADAM10 protein under basal condition and failed to further prevent KEN‐induced enhancement of ADAM10 protein levels (Figure 2D,E ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations